TARGET AND HISTORY OF ITS DEVELOPMENT - Abdul Wahab Syakhrani; Nurul Hidayah, Khairunnisa (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2022)
In the beginning, the tarekat was a form of worship practice that was taught specifically to certain people. For example, the Prophet taught wirid or remembrance that Ali ibn Abi Talib needed to practice. Then the emergence of the tarekat itself began with the classification between shari'a, tahriqat, haqiqat, and makrifat by the Sufis. It was only in the 5th century Hijriyah or 13 AD that the tarekat emerged as a continuation of the thoughts of the Sufis.